Ballads and songs of Peterloo - Morgan, Alison (Manchester University Press, 2018)
This is an edited anthology comprising more than seventy poems and songs written in immediate response to Peterloo in 1819. Mainly anonymous, these ballads appear either as broadsides or in the radical press and are collected together for the first time.